The drivers and barriers influencing the commercialization of innovations at research and innovation institutions in Uganda: a systemic, infrastructural, and financial approach - Jjagwe, Ronald; Kirabira, John Baptist; Mukasa, Norbert; Amanya, Linda (Springer Berlin Heidelberg, 2024)
Research and innovation (R&I) institutions must commercialize their innovations to remain competitive in a knowledge-based economy. While R&I institutions in Uganda have the potential to drive socioeconomic development, a clear understanding of the commercialization pathway is lacking. This study aims to bridge this gap by analyzing the systemic, infrastructural, and financial factors that drive and hinder the commercialization of innovations at R&I institutions in Uganda. This study offers the first comprehensive examination of the systemic, infrastructural, and financial dimensions influencing innovation commercialization within Uganda's R&I ecosystem, presenting new empirical evidence on the prioritized barriers and drivers as perceived by key stakeholders. Employing a mixed-method approach, this study uniquely combines quantitative surveys with qualitative case studies and key informant interviews, enabling a nuanced understanding of the multifaceted drivers of and barriers to innovation commercialization in Uganda. The study employed the Delphi technique to identify consensus among key informants. The findings highlight the urgent barriers to address, including fragmented R&I ecosystems, inadequate support infrastructure, such as technology transfer offices, and significant gaps in innovation financing. These issues underscore the urgent need for targeted policy interventions. Based on our findings, we recommend the establishment of a national innovation fund, enhancement of public private partnerships for R&D infrastructure development, and formulation of a cohesive national policy framework to streamline commercialization processes at R&I institutions. This study provides policymakers with a data-driven foundation to craft targeted interventions aimed at removing the identified barriers, thereby catalyzing the commercialization of innovations in Uganda's R&I institutions.